Factors associated with postnatal depression at Levai Mbatha Community Healthcare Centre Evaton, Sedibeng District - Phukuta, Nyundu (My University, 2019)
Introduction Depression is a significant cause of disability globally, and approximately one in five women will experience an episode of depression during pregnancy and/or the postnatal period. Despite it being a common postnatal psychiatric condition with an important impact on not only the mother and child but also the family, postnatal depression (PND) has received only little attention in developing countries. This study aimed to determine the point prevalence and factors associated with PND among postnatal mothers attending Levai Mbatha clinic, in Gauteng South Africa. Method This cross-sectional study was conducted among 227 consecutively recruited mothers who attended the postnatal clinic. A researcher-administrated Edinburg Postnatal Depression Scale (EPDS) questionnaire was used to collect information on mothers’ mental state. In addition, socio-demographic and clinical information was also obtained. Analysis was done using descriptive statistics, chi square test and logistic regression. A score of more than 13 on the EPDS was considered positive for PND. Results Participants’ mean age was 27 years. More than half (52.4%) did not complete secondary school education, were single (55.5%), and employed or had an employed partner (60%). Using the EPDS, the point prevalence of PND was 38.8%. Most participants had no medical illness (67%) or previous PND (97%), were breastfeeding (88%), and had an unplanned pregnancy (58%). More than a third had a negative view of pregnancy or the sex of the child (37% and 34%, respectively). Most participants reported having had a favorable delivery (93%), were in a monogamous relationship (85%), and were financially supported by their partner or family (85%). Mothers who only completed primary school were significantly more likely to have PND (OR: 9.11; 95% CI: 1.03-80.22) than others. Mothers who used contraceptive methods prior falling pregnant were twice more likely to have PND compared to those who did not (OR: 2.05; 95% CI 1.12-3.72; p= 0.019). The likelihood of having PND was significantly lower for the mothers who iv had a relationship with the father of the index child compared to mothers who did not have relationship with the father of the index child (OR: 0.42; 95% CI 0.18-0.94; p= 0.037). Mothers who had ever thought of harming themselves or the baby were 22 times more likely to have PND. Conclusion This study found that PND is highly prevalent in the study setting. While this underscores the need for routine screening for PND in the parturient in the postpartum period, interventions aimed at addressing PND need to be cognizant of the influence of unstable relationship between the mother and the father, low level of education, contraception failure and thoughts of self-harm on the development, assessment and management of PND.
A research report submitted to the Faculty of Health Sciences in partial fulfillment of the requirements for the degree of Master of Medicine in Family Medicine, University of the Witwatersrand, Johannesburg, 2019
Keywords: Depression; Depressive Disorder